Β-Lactam antibiotic targets and resistance mechanisms: from covalent inhibitors to substrates. Issue 10 (4th August 2021) - Mora-Ochomogo, Montserrat; Lohans, Christopher T.
Abstract : Overview of β-lactam antibiotics and the proteins with which they covalently interact, focusing on penicillin-binding proteins and serine β-lactamases. Abstract : The β-lactams are the most widely used antibacterial agents worldwide. These antibiotics, a group that includes the penicillins and cephalosporins, are covalent inhibitors that target bacterial penicillin-binding proteins and disrupt peptidoglycan synthesis. Bacteria can achieve resistance to β-lactams in several ways, including the production of serine β-lactamase enzymes. While β-lactams also covalently interact with serine β-lactamases, these enzymes are capable of deacylating this complex, treating the antibiotic as a substrate. In this tutorial-style review, we provide an overview of the β-lactam antibiotics, focusing on their covalent interactions with their target proteins and resistance mechanisms. We begin by describing the structurally diverse range of β-lactam antibiotics and β-lactamase inhibitors that are currently used as therapeutics. Then, we introduce the penicillin-binding proteins, describing their functions and structures, and highlighting their interactions with β-lactam antibiotics. We next describe the classes of serine β-lactamases, exploring some of the mechanisms by which they achieve the ability to degrade β-lactams. Finally, we introduce the l, d -transpeptidases, a group of bacterial enzymes involved in peptidoglycan synthesis which are also targeted by β-lactam antibiotics. Although resistance mechanisms are now prevalent for all antibiotics in this class, past successes in antibiotic development have at least delayed this onset of resistance. The β-lactams continue to be an essential tool for the treatment of infectious disease, and recent advances ( e.g., β-lactamase inhibitor development) will continue to support their future use.